Rape in the Republic, 1609-1725 : Formulating Dutch Identity. - Pipkin, Amanda C. (BRILL, 2013)
By examining depictions of rape in pamphlets, plays, poems, and advice manuals, this book underscores the significance of sex and gender in the construction of Dutch identity during the period of the Revolt of the Netherlands and beyond.
Keywords: Netherlands -- Politics and government -- 1556-1648.; Netherlands -- Politics and government -- 1648-1795.; Spain -- Foreign public opinion, Dutch.; Rape -- Political aspects -- Netherlands -- History -- 17th century.; Rape in literature.; Patriotism -- Netherlands -- History -- 17th century.; Group identity -- Political aspects -- Netherlands -- History -- 17th century.; Sex role -- Political aspects -- Netherlands -- History -- 17th century.; Religion and politics -- Netherlands -- History -- 17th century.; Political culture -- Netherlands -- History -- 17th century.; Pays-Bas -- Politique et gouvernement -- 1556-1648.; Pays-Bas -- Politique et gouvernement -- 1648-1795.; Viol dans la littérature.; Patriotisme -- Pays-Bas -- Histoire -- 17e siècle.; Identité collective -- Aspect politique -- Pays-Bas -- Histoire -- 17e siècle.; Rôle selon le sexe -- Aspect politique -- Pays-Bas -- Histoire -- 17e siècle.; Religion et politique -- Pays-Bas -- Histoire -- 17e siècle.; SOCIAL SCIENCE -- Criminology.; Group identity -- Political aspects; Patriotism; Political culture; Politics and government; Public opinion, Dutch; Rape in literature; Religion and politics; Sex role -- Political aspects; Netherlands; Spain; Seksueel geweld.; Beeldvorming.; Bellettrie.; Natievorming.; Nationale identiteit.; Nederland.; 1556-1795; History